Spectroscopic studies on the interaction of hypocrellin A with myoglobin. Issue 4 (2007) - Zhou Zhou, J. H. J. H.; Wu Wu, X. H. X. H.; Yang Yang, C. C.; Gu Gu, X. T. X. T.; Zhou Zhou, L. L.; Song Song, K. X. K. X.; Feng Feng, Y. Y. Y. Y.; Shen Shen, J. J.
Abstract : Experimental results of UV-visible absorption spectroscopy and fluorescence spectroscopy indicate that hypocrellin A, which has been studied in photodynamic therapy, can interact with the surface of myoglobin through hydrophobic forces, and form a complex. Based on the Stern–Volmer equation, the quenching constants of the process can be calculated to be 4.81×10 12 L mol −1 s −1 ( t =25 ° C) and 4.54×10 12 L mol −1 s −1 ( t =42 ° C) respectively, and the binding constant is 5.53×10 4 M −1 ( t =25 ° C), while the binding sites is 0.94 ( t =25 ° C). In addition, Electron paramagnetic resonance and fluorescence spectroscopic analysis suggests that that the quenching mechanism of the interaction process occurs through the electron transfer between hypocrellin A and myoglobin.